2011
DOI: 10.1159/000323680
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that Popliteal Fat Provides Damping during Locomotion in the Cat

Abstract: Current models and concepts of motor control represent the limb as a neuro-musculoskeletal system and rarely include other potentially important supporting tissues such as fascia and adipose tissue. It is possible that a normal complement of adipose tissue could contribute to the viscoelastic properties of supporting limbs and enhance stability during locomotion. The purpose of this study was to determine if the popliteal fat pad plays a role in locomotion in the cat. It is hypothesized that the fat pad limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Elastic fibres modulate the distensibility of the fat tissue when subjected to compressive stresses and its return to normal resting tensile state, whereas collagen fibres provide rigid constraints that limit overdistension of the fat pad (Kimani, 1984). Therefore, adipose tissue contributes to the viscoelastic properties of supporting limbs and enhances stability during locomotion (Falcon et al 2011). A significantly greater number of blood vessels were found in the subtalar joint capsule as well as in the deep part of the fat pad compared with the superficial part of the fat pad at the IER.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elastic fibres modulate the distensibility of the fat tissue when subjected to compressive stresses and its return to normal resting tensile state, whereas collagen fibres provide rigid constraints that limit overdistension of the fat pad (Kimani, 1984). Therefore, adipose tissue contributes to the viscoelastic properties of supporting limbs and enhances stability during locomotion (Falcon et al 2011). A significantly greater number of blood vessels were found in the subtalar joint capsule as well as in the deep part of the fat pad compared with the superficial part of the fat pad at the IER.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, adipose tissue contributes to the viscoelastic properties of supporting limbs and enhances stability during locomotion (Falcon et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the untreated limbs of these animals were used to make additional measurements for other projects, with little sign of deterioration for 2–3 hr following the completion of the experiments reported here. For example, most of these animals were used to evaluate the influence of popliteal fat on acceleration, and it was found that acceleration increased following the manipulation (Falcon et al, 2011). Furthermore, in extensive studies of locomotion in premammillary decerebrate cats, useful data were acquired for up to 3 hr (Ross & Nichols, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…In order to preclude this possibility, all trials were collected within an hour of the onset of locomotion even though most cats continued to walk for upwards of 4 hr. Following these measurements, the preparations were used for additional experiments, such as the removal of popliteal fat from the untreated limb (Falcon, Stahl, & Nichols, 2011). The success of these additional experiments indicated that the present results did not result from deterioration of the preparation (see Results section).…”
Section: Methodsmentioning
confidence: 99%
“…In the case of crural fascia disruption in cats, there is no increase in yield but rather a decrease in propulsive force . Moreover, other tissues, including adipose tissue, can alter the range of motion and increase energy expenditure [Falcon et al, 2011]. The researchers concluded that the popliteal fat may contribute to limiting angular acceleration of the knee which is beneficial unless there is too much fat.…”
Section: Non-neural Factors Affect Locomotion As Well As Posture and mentioning
confidence: 99%